2020
DOI: 10.3390/f11050577
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Biochemical Traits in Korean Pine Somatic Embryogenesis

Abstract: Korean pine broadleaf mixed forest is an important ecosystem for maintaining biodiversity in Northeast China. Korean pine is also an important species for the production of timber and nuts in the mountainous areas of Northeast China. In this study, we compared three types of Korean pine callus and found that embryogenic callus had high amounts of storage substances (protein, sugar and starch). Non-embryonic callus had high levels of polyphenols and polyphenol oxidation, while callus that lost somatic embryogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 49 publications
2
36
0
Order By: Relevance
“…As expected, the average content of IAA and ZR on the graft interface of pecan was significantly higher than in the control at 14 -31 DAG, which was consistent with cambial growth and vascular differentiation (Mo et al 2017). The IAA response mainly occurred in the pericycle, while cytokinin acts both in the pericycle and vascular cambium, and it is the major hormonal factor in regulating cambial activity (Nieminen et al 2008, Melnyk et al 2018. Moreover, IAA and ZR content in the graft union sharply increased relative to those in the control at 14 -18 DAG, thus it seems that the two hormones have distinguishing but synergetic effects on improving cambial activity, which has been demonstrated by Immanen (2016).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…As expected, the average content of IAA and ZR on the graft interface of pecan was significantly higher than in the control at 14 -31 DAG, which was consistent with cambial growth and vascular differentiation (Mo et al 2017). The IAA response mainly occurred in the pericycle, while cytokinin acts both in the pericycle and vascular cambium, and it is the major hormonal factor in regulating cambial activity (Nieminen et al 2008, Melnyk et al 2018. Moreover, IAA and ZR content in the graft union sharply increased relative to those in the control at 14 -18 DAG, thus it seems that the two hormones have distinguishing but synergetic effects on improving cambial activity, which has been demonstrated by Immanen (2016).…”
Section: Discussionsupporting
confidence: 80%
“…As one of the main signalling molecules, indole-3-acetic acid (IAA) accumulation directly activates vascular differentiation and reconnection (Yin et al 2012, Melnyk et al 2018. Vessels and sieve tubes are normally differentiated from the vascular cambium, and cambial activity is largely regulated by cytokinins (Nieminen et al 2008, Aloni et al 2010. Studies on grafted apple have shown that abscisic acid (ABA) can effectively alter xylem development and reduce hydraulic conductance, which induces dwarfing Fazio 2011, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…(Yang et al, 2020). Scott et al (1995), studying the metabolism of maltose and sucrose in the embryogenesis of microspores isolated from Hordeum vulgare L., reported a higher assimilation of carbon in the culture medium, containing sucrose than in those containing maltose, probably because sucrose is well assimilated in both gymnosperms and angiosperms (Ameri et al, 2020;De Sousa et al, 2020;Peng et al, 2020;Shirin et al, 2020). However, different authors have shown controversial results; in this sense, Scott et al (1995) associated the induction of embryogenesis with lower rates of substrate accumulation obtained from culture media containing maltose, and Carrion Pereira et al (2019) described maltose as more efficient than sucrose to regenerate Urochloa brizantha cv.…”
Section: Discussionmentioning
confidence: 99%
“…Picholine Marocaine and Dahbia. In the case of other plant species, such as Cucurbita pepo , the embryogenic lines showed a POX activity approximately 20 times higher than that of the nonembryogenic line [ 56 ]. In Pinus koraiensis , the activities of POXs and catalase trended upward during early somatic development [ 57 ].…”
Section: Discussionmentioning
confidence: 99%